1994
DOI: 10.1002/mrm.1910320210
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative in vivo tissue sodium concentration maps: The effects of biexponential relaxation

Abstract: The biexponential relaxation behavior of the sodium nucleus affects the accuracy of quantitative measurement of in vivo tissue sodium concentration (TSC). Theoretical analysis and in vivo experimental results are used to demonstrate the extent of the large bias in the measured TSC that arises when the relaxation behavior in vivo differs significantly from that of the calibration standards which is when a significant fraction of the total sodium signal decays with a relaxation time much shorter than the echo ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 12 publications
2
51
1
Order By: Relevance
“…Each of these limitations have been addressed in other reports (29)(30)(31). They have not been applied in the current study which was completed before those modifications were available.…”
Section: Discussionmentioning
confidence: 78%
“…Each of these limitations have been addressed in other reports (29)(30)(31). They have not been applied in the current study which was completed before those modifications were available.…”
Section: Discussionmentioning
confidence: 78%
“…Physiological processes associated with the infraction may result in exchange or redistribution of chloride ions between compartments with very short and long relaxation times, thus giving a contribution to the 35 Cl signal intensity in the MR images which does not depend on the concentration of chloride ions. On the other hand, Boada et al (6) showed that 23 Na MRI pulse sequences with radial k-space acquisition and very short echo time of TE < 0.5 ms provide accurate estimates for the tissue sodium concentration, even if short T 2 components with T 2 $ 2 ms are present. Assuming equal mobility of sodium and chloride ions, theory predicts shorter transverse relaxation times for 35 Cl (34).…”
Section: Resultsmentioning
confidence: 98%
“…In order to detect both T 2 components, as well as for the accurate quantification of the total sodium concentration, imaging techniques with ultra-short echo times of less than 500 µs are required [1,11]. Up to now, only echo times of more than 3 ms have been realised with ECG-triggered gradient echo 23 Na-MRI techniques [12,13].…”
Section: Introductionmentioning
confidence: 99%